Warehouse and distribution automation handbook - Adams, Nicholas D (Mc Graw-Hill, 1996)
This practical guide to warehouse distribution automation techniques includes: evaluation of automation packages; strategic company plans; system justification; and equipment analysis, testing, training, and follow-up.